Urgensi dan Motivasi; Perlindungan Hukum bagi Justice Collaborator dan Whistleblower dalam Tindak Pidana Korupsi - Dwiyanti, Asti; Djabbar, Asdar (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2024)
The issue of corruption eradication in Indonesia is evident from the weak legal protection for Justice Collaborators and Whistleblowers. Although they play a vital role in exposing corruption crimes, the reality is that many of them face physical threats, psychological pressure, and intimidation, which hinder the effectiveness of law enforcement. This study aims to analyze the urgency of legal protection and understand the factors that motivate individuals to become Justice Collaborators or Whistleblowers in the context of corruption crimes in Indonesia. This research employs legal research methods with a statute approach and a conceptual approach. The findings conclude that the urgency of legal protection is crucial to ensuring the safety and active participation of Justice Collaborators and Whistleblowers in uncovering corruption cases. Moreover, their motivation is influenced by moral drives, social responsibility, and legal incentives that encourage the courage to report or testify, even when faced with significant risks. Urgency, Motivation, Justice Collaborator, Whistleblower